A novel design of ultrasonic vibration system: asymmetric structure. (1st July 2022) - Zhao, Chongyang; Wang, Zhenzhou; Wang, Xiaobo; Zhao, Bo
Abstract: This paper designs an acoustic system of asymmetrical structure based on the theory of wave. Firstly, the frequency equation of asymmetric structural horn (ASH) was obtained by wave theory, the structural dimension of ASH was calculated based on frequency equation. Then, the influence law of different structural parameters on the resonance frequency and amplification coefficient of ASH was obtained. Simulation results demonstrated that the minimum error of the resonant frequency of the designed horn was 0.16%, and the maximum error was 7.57%. Effect of the change of the horn geometry on the acoustic parameters of the acoustic system was analyzed, and the results manifest that the order of influence on the resonance frequency was l 2 > l 1 > r 2 > θ, the order of influence on the amplification coefficient was l 1 > r 2 > l 2 > θ . Finally, the variable horn was processed in segmented and integral two processing methods, and its acoustic performance was tested. Results indicated that the vibration form of the horn output was the vertical vibration accompanied by the slightly curved vibration and the longitudinal vibration amplitude of ASH with resonant frequency of 30–35 kHz can reach 5 μ m . ASH meets the requirements of amplitude in ultrasonic assisted machining and can further expand the application field of ultrasonic machining.